2014
DOI: 10.1016/j.actbio.2014.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hLF1–11 immobilization onto chitosan ultrathin films, and its effects on antimicrobial activity

Abstract: a b s t r a c t hLF1-11 (GRRRRSVQWCA) is an antimicrobial peptide (AMP) with high activity against methicillin-resistant Staphylococcus aureus (MRSA), the most prevalent species in implant-associated infection. In this work, the effect of the surface immobilization on hLF1-11 antimicrobial activity was studied. Immobilization was performed onto chitosan thin films as a model for an implant coating due to its reported osteogenic and antibacterial properties. Chitosan thin films were produced by spin-coating on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 50 publications
7
64
0
Order By: Relevance
“…This result was expected, since we previously demonstrated the antimicrobial properties of this chitosan ultrathin films [18]. Remarkably, films with adsorbed peptide (Ch_Dhvar5_ads) did not significantly differ from Ti neither from Au in total adhered bacteria, demonstrating that the adsorbed Dhvar5 induced bacterial adhesion to chitosan film.…”
Section: Viability Assayssupporting
confidence: 56%
See 2 more Smart Citations
“…This result was expected, since we previously demonstrated the antimicrobial properties of this chitosan ultrathin films [18]. Remarkably, films with adsorbed peptide (Ch_Dhvar5_ads) did not significantly differ from Ti neither from Au in total adhered bacteria, demonstrating that the adsorbed Dhvar5 induced bacterial adhesion to chitosan film.…”
Section: Viability Assayssupporting
confidence: 56%
“…Chitosan ultrathin films were produced as previously described [18]. Briefly, commercial squid pen chitosan (France Chitine) was purified by the re-precipitation method [19] resulting on a molecular weight of 283,000-472,000 with a deacetylation degree (DD%) of~85%.…”
Section: Preparation Of Chitosan Ultrathin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behavior could represent a good model for bacteremia without ongoing sepsis. Several antibacterial coatings (antibiotics, antiseptics, metal ions, non‐metal ions, or organic molecules) of implants in orthopedics have been developed, and the ability of such implants to minimize bacterial adhesion or inhibit biofilm formation has been investigated. However, we believe that to date, the antibacterial activity against hematogenous infection has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although several approaches to create bactericidal coatings (based on different AMPs, substrates and conjugation strategies) have been described, the translation to clinically relevant materials such as polyurethane is still scarce. Yu et al have recently reported a bactericidal antiadhesive coating consisting of a polymer brush conjugated with the AMP E6 on PU, in the context of urinary catheters application .…”
Section: Discussionmentioning
confidence: 99%